Sustainable railway engineering and operations - Blainey, Simon; Preston, John, 1960- (Emerald Publishing Limited, 2022)
Railways are frequently promoted as one of the most sustainable modes of transport. However, their impact will in practice be significantly affected by the ways in which they are designed, constructed, and used. This book provides a comprehensive overview of the issues involved in planning, engineering and operating sustainable railway systems. It introduces and examines a wide range of aspects of railway systems and their interrelationships with other human and natural systems. For each of these aspects it considers the key factors that affect the sustainability of the railway. Students, academic researchers and those in rail industry or related fields who are interested in railways or in transport sustainability more generally will find this to be an invaluable guide. It will be particularly helpful to those who are either relatively new to the railway context, or who have a detailed knowledge of one aspect of railways but are seeking to acquire a more holistic understanding of railway systems.
Keywords: Railroad engineering.; Railroads.; Sustainable engineering.; Sustainable transportation.; Technology & Engineering -- Civil -- Transportation.; Railway technology, engineering & trades.; elektronické knihy; electronic books